GAMBARAN STRES PASIEN GANGREN DIABETIK DI RUMAH SAKIT SANTAELISABETH MEDAN TAHUN 2023 - Syukur J. Gulo; Fani Sofia Rupi Pardede (Poltekkes Kemenkes Medan, 2023)
Stress can affect the quality of life of individuals, especially patients suffering from gangrene. The association between stress and diabetes gangrene is the clinical burden of the disease, lifestyle factors and adherence, antidepressant medications, brain structure and function, HPA axis dysfunction, sleep disturbances, inflammation, and environmental factors. Diabetic gangrene is a complication of diabetes mellitus caused by damage to necrosis tissue by embolism of large arteries in parts of the body so that blood supply stops Gangrene disease can cause complications, physical and psychological discomfort. The purpose of this study is to describe the picture of stress in diabetic gangrene patients in April-May 2023. This study uses a quantitative descriptive design with sample of 43 gangrene patients selected by purposive sampling. The instrument used in this study is the Depression Anxiety Stress Scales 21 (DASS-21). The results show that the stress level of gangrene patients is in the category of 43 respondents who have normal stress levels of 2 people (4.7), mild stress are 2 people (4.7), moderate stress are 2 people (4.7), severe stress are 14 people (32.6), and very severe stress 23 people (53.5). The conclusion of this study is that gangrenous patients experienced moderate levels of stress with the emotional dimension being the most influential factor on their stress levels. Further studies are needed to broaden understanding of the factors that can influence stress levels in gangrene patients and efforts that can be made to reduce their impact.